AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS EKSTRAK AIR DAN ETANOL DAUN BENALU (Dendrophthoe pentandra L. Miq) YANG TUMBUH PADA BERBAGAI INANG - Nina Artanti; Retno Widayati; Sofa Fajriah (Jurnal Kimia Terapan Indonesia, 2009)
Mistletoes are used traditionally in Indonesiaas medicinal plant, one of this as anticancer. Cancer isone of degenerative diseases could be triggered by toomuch free radicals in the body, whereas antioxidantcould reduced the risk of degenerative diseases.Mistletoes reposted content flavonoids which known have antioxidant activity. Mistletoe potency as drugmaterial should be studied sa the utilization ofmistletoe could be developed. Antioxidant activitytest using "DPPH free radical scavenger" methodand toxicity test using BSLT (Brine Shrimp LethalityTest) method had been conducted on water andethanol extracts of mistletoe Dendropthoe pentandra(L.) Miq.) that grown on various trees (star fruit,mango, cananga, 'duku, sour-sop, kepel, mahkotadewa, and tea). The result showed that ethanol andwater extracte-ofD, petandra on all host plants haveantioxidant activity (IC50 value between 6.4 - 51.8ug/mL). The result of toxicity test showed that ethanolextract of mistletoe on cananga, starfruit, kepel andmahkota dewa host plants have toxicity effect againstA. salina larvae with LCso value below 1000 ug/mL,nevertheless ethanol extract on others host plants andwater extract didn It give toxicity effect against A.salina larvae (LC50 > 1000 ug/mL).Key words: mistletoe, D. petandra, DPPH, antioxidant,toxicity, degenerative disea.